Analisis Perbandingan Kinerja Keuangan Perusahaan Sebelum dan Sesudah Merger dan Akuisisi - Nur Fathun Ni’mah; L.M Samryn (Postgraduate of Jayabaya University, 2015)
This study aims to analyze the differences in firm performance before and after mergers and acquisitions on corporate merger and acquisition activity. Corporate performance is measured by using financial ratio: Net Profit Margin (NPM), Return On investment (ROI), Return On Equity (ROE), Debt Ratio, Total Assets Turnover (TATO), Current Ratio (CR) and Earning Per Share (EPS). Quantitative method is used in this research, take the data of public company which had conducted mergers and acquisitions in Indonesia Stock Exchange (IDX) and announce its activity in the period 2007-2011, and analyzed using Wilcoxon signed ranks test and Manova are used to answer hypothesis. The results from this research show that study in 7 financial ratio, NPM, ROI, ROE, EPS, TATO, CR and Debt. On the acquire does not show significant differences in the comparison before and after the acquisition. But the companies that have merged ROI ratios, EPS and Debt there are significant differences before and after the merger.